6
$\begingroup$

I'm studying Laplace transformations for my differential equations class and typically there's a partial fraction decomposition involved, which can be very long and demanding for calculations by hand, if done the standard way.

I am aware of some of the tricks used to speed-up this procedure (like the usage of limits at infinity, or multiplying with denominators and taking particular values of $s$), however I am not able to apply them at this example:

$$\frac {s} {(s^2+2s+5)(s^2+4)} = \frac {\alpha s + \beta} {s^2+2s+5} + \frac {\gamma s + \delta} {s^2+4}$$

For example, if I attempt to extract a relation for $\gamma$ and $\delta$, by multiplying with $s^2+4$ and taking $s=2i$, I get and equation that involves complex numbers; that makes me feel I have not gained much in terms of number of operations.

Are there any better tricks for this example?

$\endgroup$
  • 1
    $\begingroup$ Solving an easy system of four linear equations is probably faster than thinking about tricks. $\endgroup$ – Eckhard Apr 4 '13 at 21:27
  • 1
    $\begingroup$ One ends up solving $\rm\ \gamma+2\delta =1,\ \delta -8\gamma = 0,\ $ which is very easy. Are you trying to find something simpler than that? See here for another example of a nonlinear Heaviside cover-up method. @Greg typo fixed. $\endgroup$ – Math Gems Apr 4 '13 at 21:56
  • $\begingroup$ @MathGems: shouldn't there be four linear equations in the four unknowns? $\endgroup$ – Greg Martin Apr 4 '13 at 21:59
  • $\begingroup$ @Greg My comment addresses the OP's remark about "extracting a relation for $\gamma$ and $\delta$". This gives said two equations. For a worked example see the link I gave. $\endgroup$ – Math Gems Apr 4 '13 at 22:02
  • $\begingroup$ Got it now, thanks. $\endgroup$ – Greg Martin Apr 4 '13 at 22:04
10
$\begingroup$

Let's apply the Heaviside cover-up method, nonlinear version, as described by Bill Dubuque.

$$\rm \frac{x}{(x^2\!+2x+5)(x^2\!+4)} \ =\ \frac{ax+b}{x^2\!+2x+5}\, +\ \frac{cx+d}{x^2\!+4}$$

Clearing denominators yields

$$\rm x\, =\, (x^2\!+4)(ax+b)\, +\, (x^2\!+2x+5)(cx+d) $$

Evaluating this mod $\rm\ x^2\! +\! 4\,\: $ i.e.$\:$ iteratively applying the rewrite rule $\rm\ x^2 \to -4\,\ $ yields

$$\rm x\, =\, (c\!+\!2d)\ x\,+\, d\!-\!8c\ \ \Rightarrow\ \ c = 1/17,\,\ d= 8/17$$

Evaluating it mod $\rm\ x^2\! +\! 2x\!+\!5\:,\: $ i.e.$\:$ iteratively applying rewrite rule $\rm\ x^2 \to -2x\!-\!5\: $ yields

$$\rm x\, =\, (3a\!-\!2b)\ x \,+\, 10a\!-\!b\ \ \Rightarrow\ \ a = -1/17,\,\ b = -10/17$$

That seems easy enough to me.

$\endgroup$
  • $\begingroup$ I wasn't aware of this method and I couldn't come up with it on my own. This is great, thank you. $\endgroup$ – gpo Apr 4 '13 at 22:32
2
$\begingroup$

Well, the following is certainly a trick. Whether it's better or not remains to be decided....

First, I want to make the factors in the denominator symmetric with respect to the origin (right now they're of the form $s^2+4$ and $(s+1)^2+4$, hence symmetric with respect to $1/2$). So setting $s=t-1/2$, we have the equivalent problem of doing partial fractions on $$ \frac{16 t-8}{(4 t^2-4t+17)(4 t^2+4t+17)}. $$

Let's start by noting (using the symmetry) that $$ \frac{1}{4 t^2-4t+17} - \frac{1}{4 t^2+4t+17} = \frac{8t}{(4 t^2-4t+17)(4 t^2+4t+17)}. $$ How can we divide everything in sight by $t$? Notice that the inverse of $t$ modulo $4t^2-4t+17$ is $(-4t+4)/17$, while the inverse of $t$ modulo $4t^2+4t+17$ is $(-4t-4)/17$. So we get \begin{align*} \frac{8}{(4 t^2-4t+17)(4 t^2+4t+17)} &= \frac{1/t}{4 t^2-4t+17} - \frac{1/t}{4 t^2+4t+17} \\ &\equiv \frac{-4t+4}{17(4 t^2-4t+17)} + \frac{4t+4}{17(4 t^2+4t+17)} \pmod1. \end{align*} But this (mod 1)-equivalence must actually be an equality(!): by the theory of partial fractions, the left-hand side (whose numberator has larger degree than the denominator) has a representation in the form of the right-hand side.

Between the last two identities, we see that $$ \frac{16 t-8}{(4 t^2-4t+17)(4 t^2+4t+17)} = \frac{42 t+30}{17 (4 t^2-4 t+17)}-\frac{4t+38}{17 (4 t^2+4 t+17)}; $$ now plugging $t=s+1/2$ back in yields $$ \frac s{(s^2+2s+5)(s^2+4)} = \frac{-s-10}{17 (s^2+2 s+5)}+\frac{s+8}{17 (s^2+4)}. $$

$\endgroup$
1
$\begingroup$

I know this is a late answer but I thought it would be useful. First, you can use cover up method by plugging in $x=2i$. You end up getting $$\frac{(2i+8)}{17}= C(2i)+D\implies \frac{2i}{17}= C(2i) \implies C=\frac1{17}\text{ and }D=\frac8{17}.$$ Easy as that! To get $A$ and $B$, use cover up with $x= -1+2i$ which is one of the complex roots of $x^2+2x+5$. So $$\frac{-1+2i}{(-1+2i)^2+4} = A(-1+2i)+B \implies \frac{-1+2i}{1-4i}= A(-1+2i)+B.$$ Finally multiply by conjugate and we get $$\frac{(-1+2i)(1+4i)}{17}= A(-1+2i)+B\implies\frac{-9-2i}{17}= B-A+2iA \implies -\frac2{17}=2iA \implies A=-\frac1{17}$$ and so $B-A= -\frac9{17}\implies B= -\frac1{17}-\frac9{17}=-\frac{10}{17}$. Hence $A=-\frac1{17}$ and $B=-\frac{10}{17}$.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.